2011
DOI: 10.1007/s10856-011-4449-6
|View full text |Cite
|
Sign up to set email alerts
|

Conjugation of gold nanoparticles to polypropylene mesh for enhanced biocompatibility

Abstract: Polypropylene mesh materials have been utilized in hernia surgery for over 40 years. However, they are prone to degradation due to the body's aggressive foreign body reaction, which may cause pain or complications, forcing mesh removal from the patient. To mitigate these complications, gold nanomaterials were attached to polypropylene mesh in order to improve cellular response. Pristine samples of polypropylene mesh were exposed to hydrogen peroxide/cobalt chloride solutions to induce formation of surface carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 32 publications
2
14
0
Order By: Relevance
“…It should be noted that onset temperature corresponds to the beginning of the phase transition, and is not the same as the position of the peak on DSC. Typically, onset temperatures are reported in the literature for characterization of functional polymeric materials, including hernia meshes, since these parameters correlate better with the degree of crystallinity …”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that onset temperature corresponds to the beginning of the phase transition, and is not the same as the position of the peak on DSC. Typically, onset temperatures are reported in the literature for characterization of functional polymeric materials, including hernia meshes, since these parameters correlate better with the degree of crystallinity …”
Section: Discussionmentioning
confidence: 99%
“…Utilizing gold nanoparticles to improve collagen stability can lead to other benefits as well. Recent studies have shown that gold nanoparticles will enhance biocompatibility . For example, gold nanoparticles were entrapped within a poly(ether)urethane material, which led to improved cell adhesion and protein adsorption as well as reduced monocyte activation and bacterial adhesion .…”
Section: Introductionmentioning
confidence: 99%
“…For example, gold nanoparticles were entrapped within a poly(ether)urethane material, which led to improved cell adhesion and protein adsorption as well as reduced monocyte activation and bacterial adhesion . Other studies showed that gold nanoparticles crosslinked to polypropylene improved cellularity via cell culture assays . Still others have shown that proteins important for cell adhesion adsorb at higher concentrations on nanomaterials than on conventional materials .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The collagen and elastin present in the patch matrix provides an organized scaffold for cells to adhere and proliferate [54]. In addition, the AuNPs as shown in Figure 4e have been shown to increase stability, decrease inflammation, and slow down scaffold degradation as demonstrated in earlier in vitro studies [30, 31, 34, 5557]. The lack of thrombosis and other inflammatory and immune reactions may indicate that the patches’ surface modifications are aiding in the host integration process.…”
Section: Discussionmentioning
confidence: 95%